The Influence Of Promotion Strategies Through Tiktok, Word Of Mouth, And Brand Image On The Purchase Decision Of Somethinc Products Among Students Of The Faculty Of Economics And Business At Malikussaleh University - Sara, Sara Yulis; Rahmaniar Rahmaniar; Ikramuddin Ikramuddin; Muchsin Muchsin (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study analyzes the influence of TikTok promotion, Word of Mouth (WOM), and Brand Image on the purchasing decisions of Somethinc products among students of the Faculty of Economics and Business at Universitas Malikussaleh. Data were collected from 110 respondents using purposive sampling and analyzed using multiple linear regression. The results show that all three independent variables have a positive and significant effect on purchasing decisions. These findings can serve as a reference for companies in designing effective marketing strategies.